Adsorption Of Chloramphenicol By Activated Carbon Derived From Palm Kernel Shell Via Microwave Irradiation - Luqman, Farihah (Universiti Sains Malaysia, 2021)
This study aims to synthesis activated carbon (AC) derived from palm kernel shell (PKS) to adsorb chloramphenicol (CAP) from aqueous solution. This palm kernel shell activated carbon (PKS-AC) was produced via physical activation method that involves carbon dioxide (CO2) gasification and heating process via microwave. The effects of preparation conditions of microwave radiation power and radiation time on CAP removal efficiency and AC’s yield were optimized via response surface methodology (RSM). Optimum preparation conditions for PKS-AC were identified, including radiation power of 364 W and 2 min of radiation time. These optimum conditions contributed to relatively high CAP removal of 85.93% and AC’s yield of 37.02%. Through elemental analysis, the total fixed carbon for raw PKS was found to be 40.23% and greatly increased to 71.86% (optimized PKS-AC) after activation process. The equilibrium studies which involved initial CAP concentration, contact time, the temperature of solution and pH solutions based on adsorption of CAP on optimized PKS-AC were performed. The adsorption of CAP onto optimized PKS-AC followed Langmuir isotherm where the maximum adsorption capacities were 22.83, 23.70 and 24.88mg/g for 30°C, 45°C and 60°C respectively. Kinetic studies revealed that adsorption of CAP onto PKS-AC followed pseudo-second order kinetic model while thermodynamic studies confirmed that the adsorption system was endothermic in nature. Mechanism studies described that the CAP adsorption process was govern by film diffusion mechanism model.